On the enhancement of thermal transport of Kerosene oil mixed TiO₂and SiO₂ across Riga wedge - Yahya, Asmat Ullah (2022)
Efficient thermal transportation in compact heat density gadgets is a prevailing issue to be addressed. The flow of a mono nanofluid (SiO2/Kerosene oil) and hybrid nanofluid (TiO2 + SiO2/Kerosene oil) is studied in context of Riga wedge. The basic purpose of this work pertains to improve thermal conductivity of base liquid with inclusions of nano-entities. The hybrid nanofluid flow over Riga wedge is new aspect of this work. The concentration of new species is assumed to constitute the base liquid to be non-Newtonian. The fundamental formulation of the concentration laws of mass, momentum and energy involve partial derivatives. The associated boundary conditions are taken in to account. Similarity variables are utilized to transform the leading set of equations into ordinary differential form. Shooting procedure combined with Runge-Kutta method is harnessed to attain numerical outcomes. The computational process is run in matlab script. It is seen that the velocity component f′(η) goes upward with exceeding inputs of modified Hartmann number Mh and it slows down when non-dimensional material parameter αh takes large values. Also, Nusselt number - θ′(0) is enhanced with developing values of Eckert number Ec and Biot number Bi.